2022
DOI: 10.1093/genetics/iyac008
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in effective size across the genome: effects on the inverse instantaneous coalescence rate (IICR) and implications for demographic inference under linked selection

Abstract: The relative contribution of selection and neutrality in shaping species genetic diversity is one of the most central and controversial questions in evolutionary theory. Genomic data provide growing evidence that linked selection, i.e. the modification of genetic diversity at neutral sites through linkage with selected sites, might be pervasive over the genome. Several studies proposed that linked selection could be modelled as first approximation by a local reduction (e.g. purifying selection, selective sweep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
5
22
0
Order By: Relevance
“…We assessed the performance of MSMC2 in the presence of background selection in a S. cerevisiae -like genome by simulating data with the reference gene set and deleterious mutations (see Methods). We found that compared to simulations under a purely neutral scenario (Figure 4A), background selection led to an apparent recent increase in population size despite the real population size being constant (Figure 4B), recapping the results of previous studies (Boitard et al, 2022; Johri et al, 2021). When the real demography is declining, the resulting inferred demography shows a combination of decline followed by a recent expansion.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…We assessed the performance of MSMC2 in the presence of background selection in a S. cerevisiae -like genome by simulating data with the reference gene set and deleterious mutations (see Methods). We found that compared to simulations under a purely neutral scenario (Figure 4A), background selection led to an apparent recent increase in population size despite the real population size being constant (Figure 4B), recapping the results of previous studies (Boitard et al, 2022; Johri et al, 2021). When the real demography is declining, the resulting inferred demography shows a combination of decline followed by a recent expansion.…”
Section: Resultssupporting
confidence: 85%
“…Linked selection, and in particular background selection (BgS), was shown to impact demographic inference (Boitard, Arredondo, Chikhi, & Mazet, 2022;Johri et al, 2021). Because the genome of S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seychelles' landmass is estimated to have been up to 180 times its present size, and gene flow may have been facilitated by islands in the western Indian Ocean that could have acted as stepping-stones between landmasses during the Pliocene and Pleistocene (Warren et al 2010;Cheke and Hume) This geological signature has been seen in other Seychelles taxa (Groombridge et al 2002;Rocha et al 2013;Labisko et al 2022). However, the large ancestral Ne can also be an artefact of population structure, selection and admixture, all of which are known to introduce biases to coalescent demographic reconstruction (Mazet et al 2016;Johri et al 2021;Boitard et al 2022). For example, if island populations were reproductively separated at some point, PSMC estimates would be inflated as alleles would not coalesce.…”
Section: Demography and Runs Of Homozygositymentioning
confidence: 99%
“…In fact, genetic diversity results from the balance between all the evolutionary processes at play in the species' evolutionary history (see the review of Ellegren & Galtier 2016). Other important factors can strongly impact genetic diversity, including demography and structure, but also linked selection (Boitard et al 2022;Buffalo 2021;Ellegren & Galtier 2016).…”
Section: Recommendationmentioning
confidence: 99%